Ethical considerations in natural history film production and the need for industry-wide best practice - Williamson, Michael J.; Curnick, David J.; Jacoby, David M.P.; Durant, Sarah M.; O’Neill, Helen M.K. (Global ecology and conservation, 2022)
Natural history documentary films can be a powerful tool for wildlife conservation, providing an accessible means to increase public knowledge of the natural world. There has been an increasing focus in documentary films on the threats to biodiversity in recent years that has positively aided conservation efforts. However, potential ethical and welfare implications of natural history film making are often overlooked. Here, we consider the design and impact of the narratives used and the filming methods employed in natural history film making and their potential implications for conservation. Although these programmes are often lauded for their cinematography, filming techniques and practices should satisfy high ethical standards and should be evaluated to assess disturbance caused to wildlife and any associated negative behavioural and physiological impacts. This evaluation should include the direct impact of the filming, as well as considering the risk of viewers replicating human-wildlife encounters they see on film. Trends towards the use of highly dramatized storytelling, anthropomorphism and the inclusion of inaccurate information should also be addressed. Although some production companies have filming guidelines in place, this is not standard industry practice. Natural history films are an important means of educating and enthusing people about nature and its conservation; however, it is vital that films are made responsibly. To facilitate this discussion, we propose recommendations, including standardised industry-wide guidelines, codes of conduct and independent ethical reviews, for natural history film makers to mitigate and avoid negative impacts.